2015
DOI: 10.1161/atvbaha.114.305071
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Four-and-a-Half LIM Domain Protein 2 Decreases Atherosclerosis in ApoE −/− Mice

Abstract: A therosclerosis is a chronic inflammatory disease that is characterized by modifications in the vascular, metabolic, and immune systems. The accumulation of leukocytes within atherosclerotic lesions is a process regulated at various levels, including mobilization, recruitment, and endothelial adhesion of monocytes, followed by their migration into the intima and differentiation into macrophages.1,2 Two major monocyte subsets can be distinguished in the blood based on differential expression of the chemokine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In both myeloid and vascular cells, FHL2 also plays an important role in atherosclerosis by promoting proinflammatory chemokine production, adhesion-molecule expression, and proinflammatory monocyte recruitment [ 13 ], and FHL2 deletion attenuates the formation of atherosclerotic lesions induced by a cholesterol-enriched diet [ 14 ]. Furthermore, FHL2 was originally identified in the heart, and the association of FHL2 mutations with human cardiac hypertrophy reinforce both its importance in the heart and its relevance to human cardiac disease [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In both myeloid and vascular cells, FHL2 also plays an important role in atherosclerosis by promoting proinflammatory chemokine production, adhesion-molecule expression, and proinflammatory monocyte recruitment [ 13 ], and FHL2 deletion attenuates the formation of atherosclerotic lesions induced by a cholesterol-enriched diet [ 14 ]. Furthermore, FHL2 was originally identified in the heart, and the association of FHL2 mutations with human cardiac hypertrophy reinforce both its importance in the heart and its relevance to human cardiac disease [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…19 Absence of FHL2 reduced the atherosclerotic plaque formation by regulating the inflammatory process including macrophage and monocyte recruitment and anti-inflammatory cytokine secretion. 13 The activated VSMCs undergo migration, proliferation and apoptosis. 20 A previous study showed that FHL2 deficiency with complete artery ligation enhanced neointimal formation by ERK phosphorylation and cyclin D1 increase.…”
Section: Discussionmentioning
confidence: 99%
“…FHL2 modulates BMP‐mediated VSMC phenotypic switching . FHL2 regulates the inflammatory response by decreasing pro‐inflammatory monocyte recruitment and macrophage content . FHL2 plays a critical role in various physiological and pathological processes, including proliferation and migration .…”
Section: Introductionmentioning
confidence: 99%
“…FHL2 (four and a half LIM domain protein-2) is shown to interfere with this process, leading to selective recruitment of Ly6C hi monocytes, in part through altered expression of CX3CL1 on endothelial cells, and CX3CR1 on monocytes. 41 Part of this phenotype may be related to FHL2-mediated repression of NR4A1. 42 Abnormal migratory behavior of plaque macrophages may impact the resolution of inflammation.…”
Section: Innate Immune Functionsmentioning
confidence: 99%